Missing OH reactivity in the global marine boundary layer - A. B. Thames; W. H. Brune; D. O. Miller; H. M. Allen; E. C. Apel; D. R. Blake; T. P. Bui; R. Commane; J. D. Crounse; B. C. Daube; G. S. Diskin; J. P. DiGangi; et al. (Atmospheric Chemistry and Physics, 2020)
The hydroxyl radical (OH) reacts with thousands of chemical species in the atmosphere, initiating their removal and the chemical reaction sequences that produce ozone, secondary aerosols, and gas-phase acids. OH reactivity, which is the inverse of OH lifetime, influences the OH abundance and the ability of OH to cleanse the atmosphere. The NASA Atmospheric Tomography (ATom) campaign used instruments on the NASA DC-8 aircraft to measure OH reactivity and more than 100 trace chemical species. ATom presented a unique opportunity to test the completeness of the OH reactivity calculated from the chemical species measurements by comparing it to the measured OH reactivity over two oceans across four seasons. Although the calculated OH reactivity was below the limit of detection for the ATom instrument used to measure OH reactivity throughout much of the free troposphere, the instrument was able to measure the OH reactivity in and just above the marine boundary layer. The mean measured value of OH reactivity in the marine boundary layer across all latitudes and all ATom deployments was 1.9 s−1, which is 0.5 s−1 larger than the mean calculated OH reactivity. The missing OH reactivity, the difference between the measured and calculated OH reactivity, varied between 0 and 3.5 s−1, with the highest values over the Northern Hemisphere Pacific Ocean. Correlations of missing OH reactivity with formaldehyde, dimethyl sulfide, butanal, and sea surface temperature suggest the presence of unmeasured or unknown volatile organic compounds or oxygenated volatile organic compounds associated with ocean emissions.